A Study of Anemia in Hospitalized Infants at A Tertiary Care Hospital - KS Sahana; Kutty Ghaliyah; Prabhu Anitha; Saldanha Prakash (Medsci Publications, 2015)
Background: Anemia is a significant public health problem that occurs worldwide with higher prevalence noted in children less than 3 years. Objective of the study was to determine the occur- rence, pattern and severity of anemia among hospitalized infants and the risk factors for development of anemia. Methods: This is a prospective study of hospitalized infants be- tween 6-12 months of age admitted at a tertiary care teaching hospital, Mangalore, Karnataka. between December 2013 to No- vember 2014. Results: Out of total 260 admissions during the study period 147 (56%) infants were found to be anemic with the mean age group of 9.6 months and majority of them (66%) were admitted for Resp. tract infections. Preterm delivery was seen 34.7% of cases, mater- nal anemia 55.8% , low SES in 60% , not exclusively breast fed in 78.2% , cow's milk in 76.2%, top up formula feed in 59.9%, im- proper weaning in 51%, LBW in 40%. 39% of infants had PEM. 52% of infants had moderate to severe anemia . 69.4% had micro- cytic and hypochromic anaemia. Conclusion: The Prevalence of anemia was 56% in the current study with more than 69% of anemic infants having microcytic hypochromic anaemia suggesting iron deficiency still as the major cause for nutritional anemia in infants. Improper Weaning tech- niques, Consumption of cow's milk, top-up formula feeding, Pre- term Gestation and low birth weight are important Risk factors Associated with development of Moderate to Severe Anemia in infants as noted in our study.